Study of the substrate influence in ZnO nanowires oriented growth - Cuellar Murillo, G.A. (2015)
A solution growth approach for zinc oxide (ZnO) nanowires is highly appealing because of the low growth temperature and possibility for large area synthesis. In our work, ZnO nanowires were obtained from thin films prepared on silica glass, Si (100) and Si (111) from a single and five layers spin-coating deposition of a sol?gel prepared with dihydrate zinc acetate, monoethanolamine and isopropanol. Crystallization annealing was performed at 450 °C. These films were used as seed layer to prepare ZnO nanowires/nanorods from a zinc nitrate and hexametilentetramine solution. X-ray diffraction analysis showed that nanowires/nanorods grown in Si (111) were preferentially orientated along the [002] direction.